UNICUM: a Portal to Dutch Academic Heritage - Reerink, Henriette (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2012)
The UNICUM development project, commissioned by the Academic Heritage Foundation (SAE), is being carried out by the five classic Dutch universities in 2010–11. UNICUM, short for ‘University Collections and University Museums’, has received a national government grant to create a digital portal to Dutch academic heritage. The portal will present both academic archives and museum and library collections. Images, collection metadata and items can be found on one site. The UNICUM idea is inspired by the Online Archive California. The project is important because it crosses the traditional sector boundaries between museums, libraries and archives, it creates awareness of the opportunities this cross-sectoral approach offers, and it retains the context of — and the relation between — objects within collections as a whole. Moreover, the joint effort brings to light the importance of creating metadata according to international standards to stimulate re-use and exchange of content. In addition, UNICUM has to be regarded as a technical project in which multi-level descriptions will be presented and browsed in a structured way (collections linked to objects and archives linked to separate documents). After the project is finished, the focus will shift to generating content. UNICUM aims to create structured and integrated access to academic heritage by: using international standards (CCO, CDWA Lite, Dublin Core) to stimulate exchange of metadata; examining the potential of EAD as an exchange standard for (non-archival) collections and for structuring related items; determining a common method and creating an input module for registration at collection level; formulating ‘Best Practice Guidelines’ for registration of material at collection and item level; choosing available and established thesauri which comprise all aspects of the future content; developing an integrated format for thematic and highlight descriptions; focusing on the interrelation between items on the one hand and collections as a whole on the other, and vice versa, an interrelation which tells the story of and gives meaning to cultural heritage; harvesting of the content of the aggregation by Europeana.